Physiopathological role of extracellular vesicles in alloimmunity and kidney transplantation and their use as biomarkers - Cuadrado-Payán, Elena; Ramírez-Bajo, María José; Bañón-Maneus, Elisenda; Rovira, Jordi; Diekmann, Fritz; Revuelta, Ignacio; Cucchiari, David (Frontiers in Immunology, 2023)
Antibody-mediated rejection is the leading cause of kidney graft dysfunction. The process of diagnosing it requires the performance of an invasive biopsy and subsequent histological examination. Early and sensitive biomarkers of graft damage and alloimmunity are needed to identify graft injury and eventually limit the need for a kidney biopsy. Moreover, other scenarios such as delayed graft function or interstitial fibrosis and tubular atrophy face the same problem. In recent years, interest has grown around extracellular vesicles, specifically exosomes actively secreted by immune cells, which are intercellular communicators and have shown biological significance. This review presents their potential as biomarkers in kidney transplantation and alloimmunity.